Young adults' friendships : over a network, over a drink : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy at Massey University, Wellington, New Zealand - Niland, Patricia Ruth (Massey University, 2014)
Friendship is a crucial relationship for young adults, yet their own sense-making of friendship within their everyday social lives remains under-explored. As a social practice, friendship is constituted through people’s shared meanings within everyday contexts. Two central social contexts for young adults are social networking sites (SNSs) and drinking. It was theorised that young adults bring shared friendship meanings to these contexts which, in turn, engage with their friendship practices, and these interactions are key to young adults’ understandings of friendship. The aims of this research were firstly to explore young adults’ friendships in relation to their uses of SNSs; secondly, to explore their friendships in relation to their drinking practices; and thirdly, to explore their uses of SNSs within the context of their drinking and friendships. Twelve same and mixed-gender friendship discussion groups were conducted with fifty-one New Zealand European young adults (18-25 years). Seven participants also showed the researcher their own Facebook pages in individual interviews. This method is a form of a ‘go-along’ walking tour of an informant’s significant places, adapted to navigating through an online SNS space. Foucauldian discursive analyses identified that friendship was constructed through discourses of ‘social pleasure’, ‘time and effort’, ‘protection’ and ‘self-authenticity’. These friendship discourses were enacted in particular ways within Facebook and within drinking practices, involving pleasures and tensions that threatened and challenged friendships. Friendship as ‘social pleasure’ was a primary shared meaning to appropriate Facebook, and to engage in drinking practices. Uses of Facebook, however, required friends to perform intensive friendship response, protection, privacy and identity work, and drinking also required friends’ protection from drinking harms. Friendship tensions were demonstrated in the effort required to maintain a ‘bad but good overall’ drinking night and to always have positive drinking photo displays; effectively airbrushing drinking practices offline and online. This research provides new knowledge of the complexities and work involved for young adults to ‘do’ their friendships within a technologically mediated social world, and within an entrenched societal drinking culture. This research contributes key insights for health initiatives (particularly alcohol harm-reduction strategies) that seek to promote healthier lives for young adults.
Keywords: Friendship in youth; Young adults